1999
DOI: 10.1074/jbc.274.12.8161
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Murine Double Minute Gene 2 (MDM2) Proteins Are Induced by Ultraviolet Light

Abstract: The mdm2 (murine double minute 2) oncogene encodes several proteins, the largest of which (p90) binds to and inactivates the p53 tumor suppressor protein. Multiple MDM2 proteins have been detected in tumors and in cell lines expressing high levels of mdm2 mRNAs. Here we show that one of these proteins (p76) is expressed, along with p90, in wild-type and p53-null mouse embryo fibroblasts, indicating that it may have an important physiological role in normal cells. Expression of this protein is induced, as is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 32 publications
1
63
1
Order By: Relevance
“…We previously demonstrated that, in addition to p90 MDM2 , a smaller MDM2 protein, p76 MDM2 , is expressed in wild-type mouse embryo fibroblasts (MEFs) but not in p53/mdm2-null MEFs (17). In addition, the testis expresses an alternatively spliced mdm2 mRNA that, when expressed in COS-1 cells, produces p76 MDM2 but not p90 MDM2 (17,20). Together, these observations indicate that p76…”
Section: Mdm2mentioning
confidence: 72%
See 2 more Smart Citations
“…We previously demonstrated that, in addition to p90 MDM2 , a smaller MDM2 protein, p76 MDM2 , is expressed in wild-type mouse embryo fibroblasts (MEFs) but not in p53/mdm2-null MEFs (17). In addition, the testis expresses an alternatively spliced mdm2 mRNA that, when expressed in COS-1 cells, produces p76 MDM2 but not p90 MDM2 (17,20). Together, these observations indicate that p76…”
Section: Mdm2mentioning
confidence: 72%
“…Until recently, p90 MDM2 was the only protein known to be a bona fide product of the wild-type mdm2 gene (17). It has long been known that multiple MDM2 proteins are expressed in some tumor cell lines, but it has not been clear whether these proteins are products of normal mRNAs (18,19).…”
Section: Mdm2mentioning
confidence: 99%
See 1 more Smart Citation
“…MDM2 intracellular levels are controlled by p53, which activates Mdm2 gene transcription from the P2 promoter (Barak et al, 1993;Mendrysa and Perry, 2000), thus establishing a negative feedback control of its activity. Alternative splicing as well as activation of dierent translation start sites may produce MDM2 isoforms exhibiting dierent biologic activities (Olson et al, 1993;Sigalas et al, 1996;Saucedo et al, 1999;. Furthermore, post-translational modi®cations of wild-type protein by caspase cleavage, sumoylation and ubiquitination have been described (Chang et al, 1998;Chen et al, 1997;Pochampally et al, 1998Pochampally et al, , 1999Buschmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the other model, unrepaired lesions interfere with transcription of a gene encoding a short-lived protein involved in p53's degradation (Ljungman et al, 1999). The mdm2 gene ®ts this description since p90 MDM2 is short-lived and its level is regulated through transcription (Juven et al, 1993;Wu et al, 1993;Saucedo et al, 1998Saucedo et al, , 1999. A transcription block that decreased the level of p90 MDM2 could prolong p53's accumulation in TCR-de®cient cells.…”
Section: Introductionmentioning
confidence: 99%